Double jeopardy? Caste, affirmative action, and stigma - Ashwini Deshpande (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper presents the results of an attitude survey administered to university students in India that attempts to delineate the social-psychological mechanisms of 'externalization' and 'internalization' to understand the possible consequences of stigma associated with caste-based affirmative action (AA). Despite a significant gap in entry scores at admission to a higher educational institution, no significant differences are found in the effort and academic attitudes between students from beneficiary groups and those who get admission through non-reserved/open seats. On a range of questions that evaluate externalization and attitudes towards AA, there are clear and significant differences between caste groups that reveal the presence of stigma through the externalization mechanism; that is, the tendency of peers to evaluate beneficiary performance prejudicially, indicating the prevalence of discriminatory attitudes towards students from target groups. However, there is no evidence of internalization; that is, students from beneficiary groups internalizing their peers' low evaluation, resulting in low self-esteem and lower performance. These findings suggest the need for establishing an antidiscriminatory apparatus inside higher educational institutions to counter stigmatizing attitudes and micro-aggressions against those admitted on the basis of AA.
Keywords: J71; J78; Z13; 330; affirmative action; caste; India; stigma; discrimination